Daily Performance of Adolescents with Executive Function Deficits: An Empirical Study Using a Complex-Cooking Task. (6th February 2020) - Fogel, Yael; Rosenblum, Sara; Hirsh, Renana; Chevignard, Mathilde; Josman, Naomi
Abstract : Purpose . To characterize and analyze the performance of adolescents with executive function deficits through the Children's Cooking Task (CCT) as a performance-based complex ecological assessment. Methods . Participants were 41 adolescents (aged 10–14 years) with normal intellectual function and executive function deficit profiles based on the Behavior Rating Inventory of Executive Function (BRIEF) parent reports and self-reports (BRIEF-SR) and the WebNeuro and 40 controls with typical development matched by age and gender. Participants in both groups performed the CCT, an ecological standardized complex task. Results . Significant group differences were found for all CCT outcome measures (total number of errors, task duration, and all qualitative rating variables). Significant correlations were found among children with executive function deficit profiles between the CCT performance duration and total number of errors and the BRIEF-SR subscale score. Two separate discriminant function analyses described primarily by the CCT correctly classified the study groups. Conclusion . The poor performance of adolescents with executive function deficit profiles exhibited through the standardized complex task, as well as the relationships with their executive functions, supplies better insight about their daily confrontations. Identifying how they perform may lead to development of focused interventions to improve these adolescents' daily performance, participation, and wellbeing.